2012
DOI: 10.1029/2011ja017069
|View full text |Cite
|
Sign up to set email alerts
|

Global observations of E region plasma density morphology and variability

Abstract: [1] The global morphology and variability of the ionospheric E region plasma density are estimated from satellite-based radio occultation total electron content (ROTEC) measurements. Vertical profiles of E region electron density are estimated using the inversion technique recently proposed by Nicolls et al. (2009). In this technique, the F-region contribution to each ROTEC measurement is removed using an assimilative model of the ionosphere in order to mitigate the effects of F-region gradients in the estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Above the valley region is the F 1 layer while below 95 km is the D region. The electron densities approximately track the expected local time morphology with a noon maximum [ Chu et al ., ; Moore et al ., ; Nicolls et al ., ; Pavlov and Pavlova , ; Titheridge , ]. Two different techniques were used to obtain the electron density profiles shown in Figure and for all 22 profiles of this study.…”
Section: Arecibo E Layer Campaignmentioning
confidence: 99%
See 1 more Smart Citation
“…Above the valley region is the F 1 layer while below 95 km is the D region. The electron densities approximately track the expected local time morphology with a noon maximum [ Chu et al ., ; Moore et al ., ; Nicolls et al ., ; Pavlov and Pavlova , ; Titheridge , ]. Two different techniques were used to obtain the electron density profiles shown in Figure and for all 22 profiles of this study.…”
Section: Arecibo E Layer Campaignmentioning
confidence: 99%
“…[], Nicolls et al . [], and the earlier work of Titheridge [, ]. However, as will be seen in the following subsections there is significant work still to be undertaken in order to model the E region processes accurately.…”
Section: Modeling and Comparisonmentioning
confidence: 99%
“…Nighttime and daytime ionospheric conditions in the ionospheric E layer are different from each other. Nicolls et al [2012] analyzed global morphology of E layer plasma density variability. They showed that electron density variability is much larger at night.…”
Section: Upper Error Bound On Refractivity Retrievalsmentioning
confidence: 99%
“…Noontime day-to-day ionosonde and incoherent scatter radar measurements of the E layer parameters were used by Moore et al [2006] to calculate the standard relative deviations of NmE from noontime NmE mean values in the range of 5-7% at middle latitudes for 9-27 March 1999 and 4 October -4 November 2002. Slightly larger values of NmE variability were estimated by Nicolls et al [2012] using the inversion technique from satellite-based radio occultation total electron content measurements. However, little attention has been given in these and other published morphological studies to NmE data sorting due to apparent variability of solar and geomagnetic activity.…”
Section: Introductionmentioning
confidence: 99%